Pharmacokinetics of exogenous melatonin in relation to formulation, and effects on sleep: A systematic review. (June 2021) - Moroni, Irene; Garcia-Bennett, Alfonso; Chapman, Julia; Grunstein, Ronald R.; Gordon, Christopher J.; Comas, Maria
Summary: There is conflicting evidence on the clinical efficacy of exogenous melatonin for the treatment of sleep disorders. This may be due to differences in the pharmacokinetic (PK) properties of melatonin formulations used in clinical trials. The aim of this systematic review was to understand the relationship between melatonin formulations and PK parameters and, where possible, the effects on sleep outcomes. To this purpose, we conducted a systematic review and nineteen papers were included. The studies included three melatonin transdermal formulation, thirteen oral formulations, one topical, two buccal, two intravenous and two nasogastric formulations. Seven studies investigated the effect of the melatonin formulation on sleep and six of them found a significant improvement in one or more sleep parameters. The potential for an improved controlled release formulation that delays maximum concentration (Cmax ) was identified. The different formulations and doses affect melatonin PK, suggesting that treatment efficacy maybe affected. Based on the current evidence, we are unable to provide recommendations of specific melatonin formulations and PK parameters for specific sleep disorders. Future studies should systematically investigate how different PK parameters of melatonin formulations affect efficacy treatment of sleep as well as circadian disorders.